Where the sidewalk ends : the poems & drawings of Shel Silverstein. - Silverstein, Shel (HarperCollins, 2004)
Where the sidewalk ends, Shel Silverstein's world begins. You'll meet a boy who turns into a TV set, and a girl who eats a whale. The Unicorn and the Bloath live there, and so does Sarah Cynthia Sylvia Stout who will not take the garbage out. It is a place where you wash your shadow and plant diamond gardens, a place where shoes fly, sisters are auctioned off, and crocodiles go to the dentist.